Addressing Mental Health Challenges and Non-communicable Diseases in Sub-Saharan Africa: An Analysis from Health Systems Approach - Hubert Amu; Mabel W. Dzenu; Sedinam T. Baku; David Naboare; Veronica O. Charles-Unadike; Laud A. Boateng; Elvis E. Tarkang; Frank E. Baiden (Preventive Medicine: Research & Reviews, 2024)
Non-communicable diseases (NCDs) including mental health issues are a substantial public health concern globally. This review article explores the mental health challenges of people living with other NCDs in Sub-Saharan Africa and proposes interventions to address them. The authors argue health systems challenges that perpetuate mental health challenges amongst patients with other NCDs that include inadequacy of health professionals, challenges in logistics and supplies, capacity building, poor service delivery and policies. To overcome these challenges, countries in Sub-Saharan Africa must prioritise investment in their health workforce including mental health officers, training, retention, good policy and governance, provision of medications, task shifting and resource allocation to deliver comprehensive and accessible mental health care for individuals living with NCDs. The adoption of health system approach will also help to accelerate progress towards the Sustainable Development Goal 3.4 by 2030.